Migration, human capital, and decent work: Venezuelans in Peru - Marvel Cequea, Mirza (2024)
This study explores the human capital, vulnerability and integration of Venezuelan migrants and refugees in Peru, emphasizing their difficulties in obtaining decent work and assimilating as productive members of Peruvian society. This study aims to investigate the challenges faced by Venezuelan migrants and refugees in integrating into Peruvian society as productive members. Using a descriptive and exploratory approach, data were collected via a questionnaire from 1193 Venezuelan migrants and refugees seeking assistance from an NGO in Lima, Peru. This study’s findings address a critical gap in the existing literature, revealing that despite high levels of education, many migrants struggle utilize their skills and knowledge effectively, leading to significant brain waste due to precarious employment conditions and suffering through their exposure to various vulnerabilities. These findings underscore the need for public policies and practices that address the improvement of migrants’ and refugees’ living conditions and the promotion of Decent Work.